2015
DOI: 10.3390/land4030711
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Potential of Integrated Vegetation Bands (IVB) to Retain Stormwater Runoff on Steep Hillslopes of Southeast Queensland, Australia

Abstract: Rainfall intensity is predicted to increase under a changing climate, leading to increased risks of hillslope erosion, downstream sedimentation and flooding. For many catchments used for grazing and agricultural land uses, it will become increasingly important to maintain ecohydrological functioning despite climatic extremes. One means to achieve this is through strategic reforestation using locally endemic species, in spatial configurations that effectively intercept, retain or and redistribute overland flows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…While the spatial distribution of the majority of ES was directly understandable (e.g., habitat quality, carbon sequestration, crop production, crop pollination, and water yield), the nutrient retention and sediment retention models presented a distribution dependent from the DEM, because the final output depends on gravitational models, vegetation, and soil characteristics [34,36,38,40,48,49].…”
Section: The Methodology Of Validationmentioning
confidence: 99%
“…While the spatial distribution of the majority of ES was directly understandable (e.g., habitat quality, carbon sequestration, crop production, crop pollination, and water yield), the nutrient retention and sediment retention models presented a distribution dependent from the DEM, because the final output depends on gravitational models, vegetation, and soil characteristics [34,36,38,40,48,49].…”
Section: The Methodology Of Validationmentioning
confidence: 99%
“…These are based on catchment area as defined by an upslope area of a pit-filled (coarse-resolution; 10 m) DEM. This is likely to significantly overestimate actual contributing catchment area, particularly in agricultural landscapes with banks and farm hillslopes dams harvesting surface water and low-gradient valley floors where the catchment area will be dynamic with depression storage and activation (Ryan et al, 2015;Callow and Smettem, 2009;Callow et al, 2007). Significant surface flows not recorded in this gauging network are captured and stored on hillslopes in farm dams (Ryan et al, 2015;Callow and Smettem, 2009).…”
Section: A Water Balance Approach To the Hillslope Recharge Modelmentioning
confidence: 97%
“…For low-gradient and lower-rainfall zones (< 600 mm yr −1 ), there has been little-to-no evidence of revegetation impacts on groundwater at the scale it has been implemented at Johnsen et al, 2008), but it remains a popular approach in attempts to combat salinity and provide biodiversity and ecosystem service benefits (Cramer and Hobbs, 2002;Halse et al, 2003;Pannell, 2008). Ryan et al (2015) provide an interesting paradigm to consider in the contact of this work on how hillslope vegetation and surface water management can be integrated. In the valley floor, the broad-based channel is a high-cost intervention but offers a potential to address some processes causing salinity and in some parts of the landscape.…”
Section: Managing Surface Water Drivers Of Dryland Salinitymentioning
confidence: 99%
“…Plant growth and the presence of trees changes the surface roughness. A modelling study for wide tree strips in Australia showed a strong effect on the soil moisture distribution by changes in surface roughness and infiltration capacity [103], which is missing in available integrated crop-tree interaction models.…”
Section: Surface Protectionmentioning
confidence: 99%